Comparing gender-specific suicide mortality rate trends in the United States and Lithuania, 1990-2019: putting one of the “deaths of despair” into perspective - Lange, Shannon; Rehm, Jürgen; Tran, Alexander; L. Bagge, Courtney; Jasilionis, Domantas; Kaplan, Mark S.; Meščeriakova-Veliulienė, Olga; Štelemėkas, Mindaugas; Probst, Charlotte (BMC psychiatry, 2022)
The increase in the suicide mortality rate among middle-aged adults in the United States (US) has been well documented. Aside from a few studies from the United Kingdom, it is unclear whether the suicide mortality rate trend in the US is also occurring in other developed countries. Accordingly, we aimed to compare the suicide mortality rate trends over the past 30 years in the US to a country in the European Union-Lithuania.